How Financial Literacy Enhances Financial Well-Being Among Generation Z: The Mediating Roles of Self-Efficacy and Locus of Control - Silvana Syah; Wahyu Purbo Santoso; Pustika Ayuning Puri; Goklas Siahaan; Annisa Dhamayanty (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Generation Z in Bekasi City faced challenges in personal financial management due to a consumptive lifestyle and easy access to financial technology, which could lead to financial instability if not balanced with adequate financial literacy and self-control. This study aimed to analyze the effect of financial literacy on personal financial management among Generation Z, with locus of control and self-efficacy as mediating variables. The research used a quantitative approach with the Structural Equation Modeling Partial Least Squares (SEM-PLS) method on Generation Z respondents in Bekasi City. The results showed that financial literacy had a significant effect on personal financial management, as well as on locus of control and self-efficacy. Self-efficacy had a significant effect on personal financial management and acted as the main mediating variable, while locus of control did not show a significant direct effect but still contributed to the mediation pathway. These findings confirmed that financial literacy was a dominant factor in shaping personal financial management behavior, with self-efficacy serving as a key reinforcement in improving financial decision-making among Generation Z. The implications of this study supported the importance of strengthening financial literacy and financial confidence in financial education programs for young people.